Emerging and Innovative Technologies for the Sanitization of Fresh Produce: Advances, Mechanisms, and Applications for Enhancing Food Safety and Quality - Yuqiao Jin; Achyut Adhikari (Foods)
The consumption of fresh produce has significantly increased in recent years, contributing to improved diets through the provision of essential nutrients, vitamins, and fiber. However, there has been a rise in foodborne illness outbreaks linked to fruits and vegetables, often caused by pathogens such as Escherichia coli O157:H7, Salmonella spp., and Listeria monocytogenes. These outbreaks have led to severe health consequences, including illnesses, hospitalizations, and even deaths. Once produce is contaminated by foodborne pathogens, these pathogens are difficult to eliminate. Traditional decontamination methods, such as water washes and chlorine-based sanitizers, have been widely used to address these microbial concerns. However, these methods may not be effective against pathogens in crevices or biofilms on the surface of produce, and their effectiveness varies depending on the type of produce and pathogens. Moreover, the chemicals used may raise health and environmental concerns. As a result, novel technologies for pathogen inactivation are gaining attention. These include ozone, ultraviolet light, cold plasma, pulsed light, ultrasound, microbubbles, nanobubbles, electrolyzed water, high-pressure processing, chlorine dioxide gas, and among others. This paper reviews a range of emerging and innovative technologies for the sanitization of fresh produce. The mechanisms, advancements, and practical applications of these technologies are examined with a focus on enhancing food safety and preserving produce quality. These innovative methods provide new opportunities for both research and industry to develop practical, affordable, and safe solutions for maintaining produce safety and quality. Recent studies highlight the effectiveness of combining methods, showing that using multiple sanitization techniques can significantly improve pathogen inactivation on fresh produce. For example, more than 5 log reductions of Listeria innocua and E. coli on avocado, watermelon, and mushroom can be achieved with the combined application of pulsed light and malic acid in previous research. In this review, we recommend the application of combined sanitization methods, emphasizing that integrating multiple techniques can provide a more effective and comprehensive approach to pathogen inactivation. This combined-method strategy has become a promising and innovative trend in the ongoing efforts to improve produce safety and quality.